Less is more: A review of low energy standards and the urgent need for an international universal zero energy standard. (June 2016) - Williams, Joseph; Mitchell, Rachel; Raicic, Vesna; Vellei, Marika; Mustard, Graham; Wismayer, Amber; Yin, Xunzhi; Davey, Stephen; Shakil, Muzzamil; Yang, Yuanzhang; Parkin, Anna; Coley, David
Abstract: There are in excess of 70 low or zero energy/carbon building definitions/standards in circulation around the world. However there are few zero energy or zero carbon buildings. This suggests that despite, or possibly because of, a continuing debate over definitions, aspiration has not been met by reality. In this paper the most important 35 standards are reviewed and a correlation between activity in standard generation and completed buildings is presented. Combining this with the requirement for an 80% cut in carbon emissions, a consideration of the proportion of humanity that live in countries without any standards and the ratio of new-build activity vs. pre-existing stock, leads to a conclusion that there is an urgent need for a binding international zero (rather than low) energy/carbon standard that can be adopted world-wide. It is argued this is only possible if carbon is ignored in favour of energy, and many lifecycle issues put to one side. In part this is because of changing national carbon intensities within the energy supply chain, but it is also due to unresolved issues in carbon and energy accountancy. It is hence suggested that such issues are left to optional additional local standards. Highlights: The most important 35 low energy building standards are reviewed. A poor correlation between number of standards and completed buildings is found. There is an urgent need for a binding international zero energy standard.